Palmoplantar pustular psoriasis (PPPP) is characterized by activation of the IL-17A pathway. Issue 1 (January 2017) - Bissonnette, Robert; Fuentes-Duculan, Judilyn; Mashiko, Shunya; Li, Xuan; Bonifacio, Kathleen M.; Cueto, Inna; Suárez-Fariñas, Mayte; Maari, Catherine; Bolduc, Chantal; Nigen, Simon; Sarfati, Marika; Krueger, James G.
Highlights: IL-1β/IL-6/LL-37/IL-19/IL-17A/CXCL1/CXCL2 increased in PPPP as compared to NPPPP. No significant difference of IL-23 in PPPP as compared to NPPPP. IL-22 + but not IL-17A + mast cells were higher in PPPP as compared to NPPPP. IL-17A pathway may play a more important role in PPPP than in NPPPP Abstract: Background: Palmoplantar pustular psoriasis (PPPP) is a variant of psoriasis, which has significant negative impact on quality of life. The cellular and molecular inflammatory pathways involved in PPPP have not been well studied. Objective: Study the expression of cytokines and chemokines involved in the IL-17/IL-23 axis in palmoplantar pustular psoriasis and other difficult to treat psoriasis areas (palms, scalp, elbows and lower legs). Methods: Skin biopsies were performed on a total of 80 patients with PPPP, non-pustular palmoplantar psoriasis (NPPPP), or psoriasis located on elbows, knees and scalp as well as 10 healthy subjects. RT-PCR, immunohistochemistry and flow cytometry on cells extracted from skin biopsies were used to compare PPPP to other forms of psoriasis. Results: There was a significant (p < 0.05) increase in the expression of IL-1β, IL-6, LL-37, IL-19, IL-17A, CXCL1 and CXCL2 in PPPP as compared to NPPPP. However, there was no significant difference in expression of IL-23 in PPPP as compared to NPPPP and other forms of psoriasis. The proportion of IL-22 + but not IL-17A + mast cells was higher in PPPP as compared to NPPPP (p < 0.05). Conclusion: These results suggest that the IL-17A pathway may play a more important role in PPPP than in NPPPP.